2020
DOI: 10.1111/jfs.12840
|View full text |Cite
|
Sign up to set email alerts
|

Viability of Listeria monocytogenes and Salmonella Typhimurium after isochoric freezing

Abstract: Isochoric freezing, different from isobaric (conventional) freezing, allows for storage below freezing temperatures without significant damage from ice formation. While several types of tissues have been successfully stored in sub-zero isochoric conditions, it is unknown how isochoric freezing affects pathogenic microorganisms. Thus, the objective of this study was to investigate the survival of Salmonella Typhimurium and Listeria monocytogenes at below freezing storage (<0 C) in isochoric conditions. Tested c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 23 publications
0
6
0
4
Order By: Relevance
“…However, Y&M counts for the IF juice stored at 4 and 24°C were lower than that for fresh pomegranate juice, which indicated the benefits of isochoric freezing treatment for extending the shelf life of pomegranate juice. The combination of pressure and storage at subfreezing temperatures during isochoric freezing had been previously shown to reduce native microbial populations in whole pomegranate fruits and extracted arils (Bilbao‐Sainz, Chiou, Takeoka, Williams, Wood, Powell‐Palm, Rubinsky, Wu, et al., 2022) as well as pathogens (Bridges et al., 2020). Other research groups had also reported that high pressures can reduce microbial growth in pomegranate juice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Y&M counts for the IF juice stored at 4 and 24°C were lower than that for fresh pomegranate juice, which indicated the benefits of isochoric freezing treatment for extending the shelf life of pomegranate juice. The combination of pressure and storage at subfreezing temperatures during isochoric freezing had been previously shown to reduce native microbial populations in whole pomegranate fruits and extracted arils (Bilbao‐Sainz, Chiou, Takeoka, Williams, Wood, Powell‐Palm, Rubinsky, Wu, et al., 2022) as well as pathogens (Bridges et al., 2020). Other research groups had also reported that high pressures can reduce microbial growth in pomegranate juice.…”
Section: Resultsmentioning
confidence: 99%
“…Fruits and vegetables treated in this way had been shown to keep their original freshness with minimal changes in physicochemical and nutritional properties. Isochoric technologies had also demonstrated potential for inactivating microorganisms (Bridges et al., 2020; Powell‐Palm et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Because it is a simple rigid, closed-volume device, the isochoric system can be used for preservation and microbial reduction in standard industrial chilling and freezing infrastructure without altering the present facilities. 38…”
Section: Salmonella Typhimurium and Listeria Monocytogenesmentioning
confidence: 99%
“…Previous authors had shown that IF could be an effective technology to inactivate microorganisms (Bridges et al, 2020;Powell-Palm et al, 2018) and to preserve fruits and vegetables with similar qualities to those of fresh produce (Bilbao-Sainz et al, 2018Bilbao-Sainz, Sinrod, et al, 2020;Bilbao-Sainz, Zhao, et al, 2020;). In this study, we investigated IF as a nonthermal technology to enhance the safety and shelf life of liquid foods.…”
Section: Introductionmentioning
confidence: 99%